Epidemiology of recurrent genital herpes simplex virus types 1 and 2. Issue 6 (8th December 2003) - Solomon, L; Cannon, M J; Reyes, M; Graber, J M; Wetherall, N T; Reeves, W C
Abstract : Objectives: To describe the epidemiology of type specific recurrent genital herpes, and to compare the duration of recurrent genital lesions caused by herpes simplex virus (HSV) types 1 and 2. Methods: Participants were enrolled at clinics across the United States. Adults suspected of having active genital herpes were eligible. Lesions were cultured for HSV and typed. Data from 940 participants with recurrent culture positive HSV lesions were analysed. Pearson's χ 2 and Fisher's exact tests, multivariate logistic regression models, and a stratified Cox proportional hazards model were used to compare epidemiological characteristics and lesion duration of HSV-1 and HSV-2. Results: HSV-1 was present in 4.2% of the recurrent HSV culture positive lesions. HSV-1 was most prevalent among whites (6.5%) and individuals with 0–2 recurrences in the previous year (9.1%) and, among men, in those with rectal/perirectal lesions (13.2%). Longer lesion duration was not significantly associated with virus type (hazard ratio (HR) 0.95, 95% confidence interval (CI) 0.65 to 1.38, p = 0.79), but was associated with male sex (HR 0.85, 95% CI 0.74 to 0.99, p = 0.04), and HIV seropositivity (HR 0.62, 95% CI 0.48 to 0.81, p<0.01). Conclusions: The authors found that, in the United States, recurrent genital HSV-1 is relatively rare in the STD and HIV clinic setting, especially among black people. Among men, rectal/perirectal recurrent lesions are more likely to be caused by HSV-1 than are penile lesions. In addition, lesion duration depends on sex and HIV status but not virus type. These findings shed new light on the type specific epidemiology of recurrent genital HSV, and suggest that type specific testing can inform the prognosis and management of genital herpes.